Snow accumulation from the Ferrigno ice core (F10), Bryan Coast, West Antarctica - Thomas, Elizabeth (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
This dataset provides a 308 year (1703-2010) annual snow accumulation record from the Ferrigno 2010 (F10) ice core. The 136 m core was drilled on the Bryan Coast in Ellsworth Land, West Antarctica, during the austral summer 2010/11. The record was measured using the summer peak in nonsea-salt (nss) SO4, in approximately January to December. Snow accumulation is converted to metres of water equivalent (weq - m) based on measured density profile and correcting for thinning using the Nye model, assuming vertical strain rate. Samples were measured at 5 cm resolution, corresponding to approximately eight samples per year.